Eating habits and level of physical activity in university students during the COVID-19 pandemic - Espinoza , Melanda (2023)
Since the appearance of the covid-19 pandemic, changes have been generated in the eating habits and levels of physical activity of the population and especially in university students, who in addition to staying in quarantine, must continue their studies virtually during the day and without the possibility of practicing sports or going to gyms, together with the stress generated by this new type of teaching activity, makes them a target for chronic diseases, resulting from this style in which a good diet is not practiced at all. many cases. Literature related to the eating habits and the level of physical activity of university students in the period that the pandemic lasted was reviewed to study what type of relationship there is or is not. After the different studies, it was shown that approximately 60% of the students presented adequate eating habits, being able to highlight that, of this value, 61%. Referring to physical activity, 49% of the university students presented mild physical activity, of which the female sex participated in 55%, and the male sex 56% had high physical activity. It was concluded that there is a significant relationship but the level is low between eating habits and the level of physical activity in university students during the COVID-19 pandemic.